Unofficial Minecraft lab for kids : family-friendly projects for exploring and teaching math, science, history, and culture through creative building - Miller, John; Scott, Chris Fornell (Hands-on family., 2016)
Take charge of your child's screen time and learn fun lessons in math, science, art, architecture, and game design!Balancing your child's screen time can be difficult, especially when it comes to popular open-ended video games like Minecraft. The game offers players an exploration, imagination, and creation-focused environment, but its nonlinear game structure can mean spending a lot of time in the game. Minecraft Lab for Kids includes a variety of creative exercises that explore the game's aspects and use them to teach fun, educational lessons. Begin the book by brushing up on some common Minecraft language and examining each of the four game modes: survival, creative, adventure, and spectator. Then, use this knowledge to venture off onto the six different quests that encourage child and adult participation. These "gamified" labs will allow your child to earn stickers and badges as rewards as they complete quests. You'll even learn how to screencast and narrate your own videos to share with family and friends! Unofficial Minecraft Lab for Kids provides a fun, educational gaming goals that you and your child can reach together!